Adverse Birth Outcomes and Associated Factors Among Mothers in Immediate Postpartum Period with Short and Recommended Pregnancy Interval in East Gojjam Public Hospitals, Northwest Ethiopia, 2021 - Tiringo Molla Tiruye; Tazeb Alemu Anteneh; Mulunesh Abuhay Biweta; Muhabaw Shumye Mihret (Women's Health Reports)
Background: Adverse birth outcomes are the most common public health problem in both developed and developing countries, including Ethiopia. Short pregnancy interval has an adverse effect on the growth of unborn child and newborn. In our country Ethiopia, studies are limited regarding adverse birth outcomes among mothers with short and recommended pregnancy interval. Objective: This study was aimed to assess adverse birth outcomes among mothers with short and recommended pregnancy interval, in east Gojjam public hospitals, northwest Ethiopia, 2021. Methods: A facility-based comparative cross-sectional study was conducted from November 1 to December 30, 2021. A total of 456 mothers were included in the study using systematic random sampling technique. The data were collected through face-to-face interviews using structured pretested questionnaires and chart review using a checklist. Bivariable and multivariable logistic regression model was fitted. Adjusted odds ratio with 95% confidence interval at p-value of ≤0.05 was used to declare the level of significance. Result: The overall prevalence of adverse birth outcomes was 23.9%. The magnitude of adverse birth outcomes were 29.4% and 18.4% in mothers with short and recommended pregnancy interval, respectively. Having no antenatal care visits, history of intimate partner violence, history of pregnancy-induced hypertension, inability to read and write, instrumental delivery, cesarean section, and long duration of labor were significantly associated with adverse birth outcomes. Conclusion: Adverse birth outcomes had a significant association with pregnancy interval. Designing strategies to increase women’s educational status, with emphasis on maternal and child health services, will reduce adverse birth outcomes.